Sustainable greywater management with Axonopus compressus (broadleaf carpet grass) planted in sub surface flow constructed wetlands. (September 2015) - Arunbabu, V.; Sruthy, S.; Antony, Ignatius; Ramasamy, E.V.
Abstract: The scarcity of freshwater has emerged as one of the most pressing problems of the 21st century. This problem could be addressed partially by collection, treatment and reuse of greywater. In this context, constructed wetlands (CWs) become attractive due to their simple mode of operation, effectiveness in treatment and applicability at small/single household levels as well as in community levels. Hence the present study investigates the treatment of greywater in a laboratory scale horizontal sub-surface flow constructed wetland planted with Axonopus compressus (Sw.) P. Beauv. – a common landscape plant. The experiment was conducted for a period of 50 days with change in wastewater every 10 days (1 run). During each run the wastewater was circulated using a peristaltic pump at an HRT of 7.8 h. The results show that CWs planted with A. compressus performed well in the treatment of greywater than the unplanted control with an average removal of 93% turbidity, 95% COD, 98% NO3 − –N, 67% PO4 3− –P, and 95% of anionic surfactants. The plant also survived well with increase in biomass and number during the experiment and proved to be an efficient bioagent suitable for the treatment of greywater in CWs. The study further suggests that the use of commercially valuable ornamental plants in the CWs as bioagents will improve the aesthetic beauty, public acceptance and help to generate revenue apart from the major benefit of wastewater treatment.